2018
DOI: 10.1038/s41598-018-28708-z
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Uptake and Bioavailability of Tocotrienol-Rich Fraction in SIRT1-Inhibited Human Diploid Fibroblasts

Abstract: Tocotrienol-rich fraction (TRF) is palm vitamin E that consists of tocopherol and tocotrienol. TRF is involved in important cellular regulation including delaying cellular senescence. A key regulator of cellular senescence, Sirtuin 1 (SIRT1) is involved in lipid metabolism. Thus, SIRT1 may regulate vitamin E transportation and bioavailability at cellular level. This study aimed to determine the role of SIRT1 on cellular uptake and bioavailability of TRF in human diploid fibroblasts (HDFs). SIRT1 gene in young … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 61 publications
(64 reference statements)
2
9
0
Order By: Relevance
“…Thus, the bioavailability of vitamin E in the nervous system allows it to carry out its functions [ 6 ]. The current study also complements the findings of a study on the cellular uptake of vitamin E in cultured liver cells, corroborating that the structures of neither vitamin E nor α-TTP play a role in mediating the distribution of vitamin E either in the form of tocopherol or tocotrienol [ 40 ]. It may be mentioned here that other genes related to vitamin E binding (i.e., SEC14L2 , PI-TPNA , and TTPA) are involved in active vitamin E trafficking rather than being only based on passive diffusion, as suggested by Irías-Mata et al [ 26 ].…”
Section: Resultssupporting
confidence: 85%
“…Thus, the bioavailability of vitamin E in the nervous system allows it to carry out its functions [ 6 ]. The current study also complements the findings of a study on the cellular uptake of vitamin E in cultured liver cells, corroborating that the structures of neither vitamin E nor α-TTP play a role in mediating the distribution of vitamin E either in the form of tocopherol or tocotrienol [ 40 ]. It may be mentioned here that other genes related to vitamin E binding (i.e., SEC14L2 , PI-TPNA , and TTPA) are involved in active vitamin E trafficking rather than being only based on passive diffusion, as suggested by Irías-Mata et al [ 26 ].…”
Section: Resultssupporting
confidence: 85%
“…Furthermore, as the bioavailability of vitamin E represents its biological activity, the homeostasis of this vitamin in the cell is tightly regulated to prevent toxicity and alteration to the biological system. A previous study showed that the uptake of TRF in senescent cells was higher than in young cells [44]. A similar finding was observed in elderly people, which showed higher uptake of TRF as compared to the young age group [43].…”
Section: Discussionsupporting
confidence: 74%
“…TRF naturally exists as a mixture of various forms of vitamin E; all tocotrienol forms are present and highly concentrated in TRF. However, each cell has its own preference for various forms of vitamin E. A previous study showed that the concentration of α- and δ-tocotrienol was the highest in myoblasts, [ 18 ] while γ- and δ-tocotrienol were the most abundant forms in fibroblasts [ 47 ]. As previously described, TRF treatment showed a better effect than single isomer treatment.…”
Section: Discussionmentioning
confidence: 99%